2016
DOI: 10.5005/jp-journals-10030-1156
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Serum C-reactive Protein and D-lactate: Predictors of Strangulation in Intestinal Obstruction

Abstract: Introduction: Serum C-reactive protein (CRP) and D-lactate have been proposed as markers of intestinal ischemia. The purpose of this prospective observational study is to find whether serum CRP and serum D-lactate can help in predicting strangulation in cases of acute intestinal obstruction. Materials and methods:A total of 50 consecutive patients were included in the study after excluding patients of comorbid medical illness and patients with findings other than obstruction or strangulation. The serum values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
2
3
0
3
Order By: Relevance
“…For predicting strangulation, using a cutoff value of 60 mg/L for CRP, the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 87.5, 58.3, 48.3, and 91.3% respectively. 9 In our study mean D-lactate level was 5.2±0.62 mmol/L in group A and mean D-lactate level was 2.87±1.04 mmol/Lin group B. The mean D-lactate level differences in both groups were statistically significant.…”
Section: Discussionsupporting
confidence: 44%
“…For predicting strangulation, using a cutoff value of 60 mg/L for CRP, the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 87.5, 58.3, 48.3, and 91.3% respectively. 9 In our study mean D-lactate level was 5.2±0.62 mmol/L in group A and mean D-lactate level was 2.87±1.04 mmol/Lin group B. The mean D-lactate level differences in both groups were statistically significant.…”
Section: Discussionsupporting
confidence: 44%
“…There were some studies evaluated the promising clinical value of D‐lactate measurements in patients with acute abdomen and concluded an improvement in the diagnosis of acute intestinal ischemia 18,19 . Also, another study revealed an increased values of serum D‐lactate in patients had strangulated bowel obstruction 20 . Unfortunately, rarely D‐lactate levels raised during the early phase of intestinal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…В отличие от L-лактата, являющегося продуктом метаболиз-ма клеток организма человека, его повышение указывает на нарушение целостности кишечной стенки. Однако проведенные эксперименталь-ные и клинические исследования показали, что уровень D-лактата имеет низкие показатели специфичности (20%) при высокой чувстви-тельности (до 90%) [27,30,31]. Кроме этого, повышение в крови D-лактата указывает на уже состоявшийся некроз кишки, что ухудшает прогноз этой категории пациентов.…”
Section: биохимические маркеры острой интестинальной ишемииunclassified
“…Авторами показано, что чувствительность D-лактата выше, чем С-реактивного белка, однако ни у того, ни у другого не получено достаточных для использования в клинике по-казателей чувствительности и специфичности. В связи с этим авторы предлагают использовать эти два показателя вместе [31].…”
Section: биохимические маркеры острой интестинальной ишемииunclassified
See 1 more Smart Citation